Revitalisasi Community Policing: Membangun Peradaban dan Keteraturan Sosial melalui Kepercayaan dan Kolaborasi di Wilayah Perkotaan - Firman, Afryanti; Dharma, Surya (Al-'Adl, 2025)
Handling social conflicts in urban areas requires a police approach that is not only repressive, but also preventive and participatory. Community Policing is a police strategy that emphasizes the partnership between the National Police and the community in maintaining security and social order. However, in practice, the implementation of Community Policing in urban areas still faces various challenges, such as low public trust in the authorities, lack of citizen participation, and weak consistency of implementation in the field. This research aims to examine the role of Community Policing revitalization in building civilization and social order through increasing trust and collaboration between the National Police and urban communities. Using a qualitative approach and case studies in several major cities in Indonesia, this study found that Community Policing revitalization based on transparency, two-way communication, and community empowerment has been proven to be able to improve the performance of the National Police and strengthen a sense of security and togetherness in urban environments. The results of this study recommend strengthening the capacity of POLRI personnel in social communication, developing a sustainable community participation system, and policy reforms that support long-term collaboration between officials and city residents. Thus, Community Policing is not only a security strategy, but also an important pillar in the development of an inclusive and orderly urban civilization.